Digital solutions for managing climate risks and food security in Guatemala - Müller, A. (2019)
Bioversity is leading a consortium that is supporting the Guatemalan government in developing and implementing a community-based food security information and decision support system through a participatory, demand-driven co-design process. The digital solutions for managing climate risks and food security are responding to needs to improve management and response of situations of acute food insecurity related to drought.